Analytical correlation between overall subjective satisfaction and criterion-based evaluation in continuing medical education: A cross-sectional study of associated factors - Hela Ghali; Asma Ben Cheikh; Sana Bhiri; Latifa Lassoued; Imed Chouchen (PLoS ONE, 2026)
Background Continuing Medical Education (CME) is essential for updating the competencies of healthcare professionals. As part of a quality improvement initiative, the CPD committee at the Faculty of Medicine of Sousse evaluated the 2021–2022 programs. The study aimed to assess learner satisfaction by distinguishing overall subjective satisfaction from criterion-based evaluation (based on specific quality criteria like resources and pedagogy). This approach identifies whether a positive general feeling masks structural deficiencies in course design. Methods We conducted a cross-sectional study over a five-week period using a structured evaluation grid distributed via Google Forms. The evaluation covered all three phases of the CME process (before, during, and after the course). For each criterion, participants selected one of four options ranging from “unsatisfied” to “satisfied.” Criterion-based evaluation was assessed via an overall rating from 1 to 5, with a score ≥4 indicating satisfaction. Correlation between overall subjective satisfaction and criterion-based evaluation was analyzed. Results A total of 268 responses were collected. Women predominated (73.1%). The mean age was 36 ± 8 years, and most participants practiced in urban areas (91%) and at the tertiary care level (55.6%). The overall mean satisfaction score was 3.8 ± 1.02, with 69.4% of participants classified as satisfied. Overall subjective satisfaction was significantly associated with criterion-based evaluation across all criteria. In addition, overall subjective satisfaction was associated with age (p = 0.007), years in current practice (p = 0.043), academic affiliation (p = 0.008), specialty (p = 0.019), and type of CME (p = 0.003). Conclusion Learner satisfaction with CME activities was correlated with factors such as specialty, academic affiliation, experience, age, and CME format. These findings support recommendations to tailor CME content to participant profiles, emphasize practical training, ensure timely delivery of resources, and improve advance communication of schedules to enhance program effectiveness.